Ethics Vs Convenience: Islamic Education Integrated with Generative Artificial Intelligence (GenAI) - Kurniawan , Agus (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Abstract: This study aims to explore the advantages and limitations of implementing GenAI technology in Islamic education on campus, as well as to examine the role that lecturers can play in integrating GenAI technology into Islamic education on campus. The research method employed is a descriptive qualitative approach, incorporating a literature review. The results of the study indicate that the use of GenAI technology in Islamic education on campus has several advantages: 1). improving the quality and involvement of learning, 2). encouraging new competencies, and 3). supporting curriculum redesign. However, the implementation of GenAI technology is not free from limitations. The main challenges include: 1). ethical risks and academic integrity, 2). access gaps, and 3). skills, and limitations of frameworks and regulations. The roles that lecturers must take in implementing GenAI technology are: 1). Becoming a facilitator and manager of learning, 2). actively involved in designing a curriculum that integrates GenAI, 3). responsible for equipping students with AI literacy skills, critical thinking, and ethical awareness in using GenAI, and 4). participating in training and professional development to be able to utilize GenAI optimally in line with the vision of holistic Islamic education.